Effects of Substituting Soybean Meal With Winged Bean on Growth, Physiological Function and Flesh Quality of Indian Butter Catfish (Ompok bimaculatus) - Jaya Angom; Soibam Khogen Singh; Ayam Gangarani Devi; Pronob Das; Pradyut Biswas; Gusheinzed Waikhom; Soibam Ngasotter; Reshmi Debbarma; Sourabh Debbarma; Nitesh Kumar Yadav (Aquaculture Nutrition)
Soybean meal (SBM) remains a primary protein source in aquafeeds. This study investigated the potential of winged bean (Psophocarpus tetragonolobus) meal as a SBM replacement in diets for butter catfish (Ompok bimaculatus) juveniles (mean weight: 1.24 ± 0.23 g). A response surface methodology (RSM) optimized processing conditions to minimize antinutritional factors (ANFs) in winged bean meal (WBM), resulting in minimized tannin (4.14 ± 0.018 mg/g at 40 min, 110°C), phytate (0.414 ± 0.0009 mg/g at 31.67 min, 104.5°C) and trypsin inhibitor activity (70.8 ± 0.06% inhibition at 20 min, 90°C). Experimental diets containing 30% crude protein and varying levels of WBM substitution (0%, 25%, 50%, 75% and 100%) were fed for 70 days. Growth performance, measured by weight gain, was significantly higher in the 25% substitution group (p<0.05) but not significantly different from the control at 50% substitution. Quadratic regression analysis predicted an optimal inclusion level of 15.10% for maximizing weight gain. Survival rates did not differ significantly among treatments (p>0.05). Feed utilization was most efficient in the 25% substitution group. Haematological and immunological parameters indicated improved fish health at the 25% substitution level. Flesh quality attributes, including texture profile analysis, pH and antioxidant activity, were superior in the 25% group compared to other treatments. However, colour enhancement was more pronounced at higher inclusion levels (≥50%). While flesh pH and antioxidant activity suggested potential stress at higher winged bean inclusion levels, the 25% group showed improved values compared to the control. These findings suggest that WBM can potentially replace up to 50% of SBM in butter catfish diets, offering a promising alternative protein source. This study provides preliminary data on the feasibility and prospects of utilizing WBM in O. bimaculatus diets.